The Standardization of English in Gower’s Confessio Amantis - Zuraikat, Malek J. (Dirasat: Human and Social Sciences, 2023)
Objectives: This paper aims at showing how the metrical regularity of Gower’s Confessio Amantis contributes to the standardization of Middle English language, which is known for its irregularity and lack of authority compared to French and Latin. Methods: The paper analyzes the metrical structure of the Confessio in an attempt to provide several textual pieces of evidence showing how the poem’s deceptive regularity and monotonous repetitiveness reflect the poet’s definition of his own poem as "A bok for Engelondes sake". Results: The paper confirms that the poem is a novel project at the service of England through its contribution to the standardization of lewd Middle English. Also, it finds that Gower uses the techniques of rich rhyme, sight rhyme, rhyme repetition, and sentence inversion to regularize the varieties of Middle English and pave the way for its standardization. Conclusion: Against the conventional viewpoint concerning the overt regularity of Gower’s Confessio Amantis, the paper concludes that Gower deploys several linguistic and stylistic devices to incorporate the several variations of Middle English into one harmonious linguistic system, which explains why the poem is identified by its own poet as "A bok for Engelondes sake".